Sokratejska praktyka "troski o siebie" (epimeleia heautou) a proces coachingowy = The Socratic practice of "care of the self" (epimeleia heautou) and the coaching process - Kroczak, Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper I present a comparative analysis of the knowledge discovery process applied by Socrates and the contemporary coach. The term "care of the self" (epimeleia heautou) appears in the Socratic dialogues, Alkibiades I and Apology of Socrates, and this term is compared with the coaching idea of "being resourceful".
Keywords: Sokrates (filozof grecki; 469 p.n.e.-399 p.n.e.); coaching; bycie w zasobach; epimeleia heautou; relacja coachingowa; resourceful state; coaching relationship